2016
DOI: 10.7717/peerj.1955
|View full text |Cite
|
Sign up to set email alerts
|

First applications of a targeted exome sequencing approach in fetuses with ultrasound abnormalities reveals an important fraction of cases with associated gene defects

Abstract: Background. Fetal malformations and other structural abnormalities are relatively frequent findings in the course of routine prenatal ultrasonographic examination. Due to their considerable genetic and clinical heterogeneity, the underlying genetic cause is often elusive and the resulting inability to provide a precise diagnosis precludes proper reproductive and fetal risk assessment. We report the development and first applications of an expanded exome sequencing-based test, coupled to a bioinformatics-driven… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 42 publications
(54 reference statements)
3
47
0
1
Order By: Relevance
“…There are a few reports of whole exome or genome sequencing being used for diagnostic purposes in the prenatal setting when congenital malformations are identified during prenatal scans. [30][31][32][33] Our study confirms the value and diagnostic potential of next-generation sequencing in fetal medicine. It also demonstrates that whole exome sequencing can successfully be performed on fetal DNA (from amniotic cells) that has been whole genome amplified.…”
Section: Discussionsupporting
confidence: 75%
“…There are a few reports of whole exome or genome sequencing being used for diagnostic purposes in the prenatal setting when congenital malformations are identified during prenatal scans. [30][31][32][33] Our study confirms the value and diagnostic potential of next-generation sequencing in fetal medicine. It also demonstrates that whole exome sequencing can successfully be performed on fetal DNA (from amniotic cells) that has been whole genome amplified.…”
Section: Discussionsupporting
confidence: 75%
“…This is echoed in a study by Carss et al (2014), where exome sequencing was performed on 30 fetuses and newborns with a variety of ultrasound anomalies and determined a diagnostic yield of 10% over conventional chromosomal microarray analysis (CMA). Other studies have reported definitive or likely definitive diagnoses in approximately 20-40% of fetuses with sonographic abnormalities, with the wide range likely due to small cohorts (Drury et al 2015;Pangalos et al 2016;Vora et al 2017;Westerfield et al 2015). Laboratories in the USA performing clinical prenatal exome sequencing have also presented initial data with a comparable or higher diagnostic yield to exome sequencing performed in a postnatal setting (Alamillo et al 2015;Walkiewicz 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Exome sequencing on prenatal samples from ongoing or terminated pregnancies with fetal anomalies is being conducted on both a clinical and research basis. Although these early reports include relatively small numbers of cases, typically under 30 samples, results indicate exome sequencing can improve the prenatal diagnosis rates for fetuses with ultrasound anomalies not explained by conventional karyotype or CMA (Alamillo et al 2015;Drury et al 2015;Pangalos et al 2016;Vora et al 2017;Walkiewicz 2016;Westerfield et al 2015). While the American College of Medical Genetics and Genomics (ACMG) has published guidelines addressing some of the challenges from utilizing exome sequencing such as the return of secondary findings, the authors do not address prenatal or preconception sequencing (Berg et al 2011;Kalia et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…12 Research relating to the use of genetic sequencing for prenatal diagnosis in ongoing pregnancy is limited 4 ; however, the feasibility of WES in prenatal diagnostics has been demonstrated in small case series. 3,12,13 Survey data involving 186 expectant parents in the USA demonstrated that 83% thought that prenatal WES should be offered, 14 and research into the views of 15 women with noncontinuing anomalous pregnancies found that they had high hopes and expectations of WES, despite testing enabling a diagnosis in only 1 in 3 (30% of cases). 15 Successful implementation of WES for prenatal diagnosis would require rigorous health economic assessment and would be dependent upon the development of rapid analytical and interpretation pipelines.…”
Section: Several Studies Involving Wes In Patients With Mendelian Dismentioning
confidence: 99%